When voice fades, images speak; imaging diagnosis of recurrent laryngeal nerve palsy on fdg pet-ct - Nadia Nazir; Ayesha Zubair; Aamna Hassan; Kashif Saddique (Journal of the Pakistan Medical Association, 2026)
Vocal cord palsy may reveal underlying sinister pathology. Unilateral vocal cord palsy can be detected incidentally on FDG PET-CT scan performed for oncologic evaluation. There may be asymmetrically increased FDG uptake in the contralateral vocal cord due to compensatory hyperactivity and hypertrophy, along with dilatation of the affected laryngeal ventricle, consistent with vocal cord paralysis. PET-CT also aid in identifying the underlying etiological lesion along the course of the recurrent laryngeal nerve. Awareness of these characteristic imaging features is essential to prevent misinterpretation as primary laryngeal malignancy. This case highlight the integral role of FDG PET-CT in assessing the causes of vocal cord palsy. Keywords: Vocal cord palsy, PET-CT scan, Lung cancer, Mediastinal mass.